STRATEGIC HUMAN RESOURCE MANAGEMENT PRACTICES OF WESTERN MNES IN AFRICA: STANDARDIZATION, LOCALIZATION OR BOTH? - Azungah, T. (University of Jaffna, 2017)
When Western multinational enterprises seek to transfer their preferred strategic human resource management (SHRM) practices to their subsidiaries in Africa, they face numerous challenges. Some of these challenges arise from Africa’s particular cultural and institutional features. In Africa, parent country nationals (PCNs) prefer to standardize SHRM practices embedded in western values while host country nationals (HCNs) prefer to localize practices in accordance with African cultural and institutional specificities. This conceptual paper analyzes research on the motives and strategies for standardization and localization of SHRM practices and develops a set of propositions on how these practices are utilized in African subsidiaries of western multinationals. On the basis of published case examples I illus trate preferences for standardization, localization and a combination of both approaches. I discuss the implications of my study in terms of future research directions and lessons for practitioners
Keywords: MNEs; Africa; HRM; HCNs; PCNs; localization; standardization; dual approach.